Regional Economic Outlook, April 2011, Western Hemisphere : Watching Out for Overheating. (Regional Economic Outlook, 2011)
Despite the recent deterioration in the global economic environment, projections for the region involve only a modest worsening of the outlook. The October 2011 Regional Economic Outlook: Western Hemisphere cautions, however, that there are severe downside risks. A sharp slowdown in Asia, for example in response to a recession in advanced economies, could impact commodity prices, with negative effects on Latin American commodity exporters. With global monetary policy likely to remain accommodative, capital flows could exacerbate overheating and amplify vulnerabilities in emerging markets. Countries with strong real linkages to the United States face a somewhat weaker outlook and should give priority to reducing public debt. Although much of the Caribbean is recovering from a prolonged recession, the outlook remains constrained by high public debt and weak tourism flows. This issue finds that policies can play an important role in mitigating the economic impact of terms-of-trade shocks, and underscores the need to rebuild policy buffers.